Cross-Sectional Study of Different Strains of Bacillus cereus among Pap Sold in Major Towns in Ihiala LGA, Anambra State (IPS Journal of Public Health, 2025)
Species of Bacillus have long been troublesome to food producers on account of their resistant endospores. Bacillus cereus is well known as a cause of food poisoning, and much more is known about the toxin produced by various strains of this species, so that it significance in such episodes is clearer. However, it is still unclear why such cases especially among locally produced foods like pap are so rarely reported.   This study was undertaken to evaluate the cross-sectional study of different strains of Bacillus species in pap sold at different towns in Ihiala Local Government Area, Anambra State. A total of 700 samples, one hundred samples each from different major towns (A, H, I, O, S, U, Z) were randomly collected from different vendors and shops at different locations and markets in Ihiala L.G.A. and screened for the presence of Bacillus cereus using standard microbiological techniques. The prevalence of the different strains encountered in the samples was also determined. The study revealed that 30.43% of the studied samples were positive to Bacillus cereus, and the occurrences of the organism were significantly (P
Keywords: Bacillus cereus; Food contamination; Pap (fermented maize gruel); Endospores; Strain prevalence; Ihiala Local Government Area